DEVELOPMENT OF ARTICULATE STORYLINE MEDIA FOR ENHANCING LEARNING OUTCOMES IN NATURAL AND SOCIAL SCIENCES AMONG ELEMENTARY SCHOOL STUDENTS - Hidayati Rofiah, Nurul; Sinta, Tria Nurchamida Abelia; Dewi, Rahmatika (UIN Sunan Kalijaga Yogyakarta, 2024)
Technology-based interactive media have yet to reach their full potential in elementary education, resulting in suboptimal learning outcomes in the natural and social sciences. This study aims to outline the development steps for interactive learning media using Articulate Storyline and to assess the quality and effectiveness of this media in teaching fifth-grade students about Earth and the Universe within natural and social science subjects. Employing a research and development approach, this study utilized the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The participants were fifth-grade students from the Muhammadiyah Elementary School of Karangbendo, Yogyakarta, with 28 students. Instruments used in this research are questionnaires and tests. The questionnaire was used to get data from the experts, whereas a test was used to get the data on learning outcomes. The findings suggest that the Articulate Storyline interactive learning media is suitable and effective, as evidenced by an average 'Highly Suitable' rating of 87% from experts in content knowledge, media, language, and teaching and learning in primary education and a 'Very Good' response rating of 98% from teachers and students. A significant improvement in learning outcomes was observed, with an average n-gain score of 0.73, indicating a high level of effectiveness. This media is recommended as an alternative for educational activities in schools, particularly for introducing topics related to Earth and the universe.